Subjective and objective outcome measures of computer-based vision restoration training. - Poggel DA; Mueller I; Kasten E; Bunzenthal U; Sabel BA (NeuroRehabilitation, 2010)
Objective: To determine the relationship of objective and subjective outcome measures of Vision Restoration Training (VRT) for visual field recovery in partially blind patients. This is of interest because the patient's subjective improvement cannot be inferred from objective changes in visual field charts. Design: Nineteen patients with visual system lesions underwent visual field tests (objective measure) before and after six months of VRT. Subjective outcome was determined by pre- and post-training interviews (open narration, questions on activities of daily living, ratings). Interview content was quantified by determining the response frequency for relevant content categories. Drawings of perceived visual field size were used as a subjective topographical measure. Subjective training results were compared to objective visual field size (perimetry). Results: Visual field size increased significantly over the training period. Patients' subjective evaluations depended on the size and location of regained areas, but also on specific evaluation of safe navigation, mobility, reading, and communication. Patients with objective increase of visual field size also reported subjective improvements in daily life. Conclusions: Computer-based training can improve visual field size as well as subjective visual performance. The patients' subjective experience should be included in treatment evaluation to ensure the meaningfulness of training beyond perimetric measures.